Epidemiology and outcomes of candidaemia among adult patients admitted at Hospital Universiti Sains Malaysia (HUSM): a 5-year review - Haydar Ali Tajuddin, Amalina (International Islamic University Malaysia (IIUM), 2018)
Introduction: Candida organisms are opportunistic fungal pathogens that have become a major cause of nosocomial infections worldwide. We investigated the clinical characteristics and outcomes of hospitalized patients with candidaemia caused by Candida albicans and non-albicans Candida spp at HUSM. Materials and Methods: We retrospectively evaluated all hospitalized patients with candidaemia from January 2010 till December 2014 based on inpatient hospital records and laboratory data. Results: A total of 134 patients with candidaemia were enrolled. Candida albicans and non-albicans Candida spp were responsible for 20% (27/134) and 80% (107/134) of candidaemia cases, respectively. Hospitalized patients with diabetes mellitus, surgical conditions, or concomitant septicaemia and those who received instrumentations such as CVC or CBD, and those admitted under medical settings were prone to develop candidaemia caused by either C. albicans or non-albicans Candida spp. All isolates were susceptible to Fluconazole except for C. krusei isolates. All-cause mortality within 30 days post diagnosis of candidaemia was 59%. Factors associated with mortality were solid tumor (p =0.014), surgical illness (p=0.128), central venous catheterization (p= 0.096) and leucocytosis (p=0.116). Only solid tumor was an independent contributory factor for mortality among patients with C. albicans candidaemia in the multivariate analyses (OR 5.09, 95% CI 1.38,18.74, p=0.014). Conclusions: The patients’ clinical characteristics were fairly comparable between Candida albicans and non-albicans candidaemia. The changing epidemiology of candidaemia at this centre was in fact alarming. The outcome associated with candidaemia was poor.